The influence of urban form on facades noise levels - Oliveira, Marta Isabela Fernandes (2011)
The urban form affects directly the natural habitats, ecosystems and the different species. Indirectly the urban form influences the behavior of the trajectory, which in turn affects the air quality, the global climate and of course the noise propagation. This paper seeks to address the problems of the urban environment as an area of interaction between urban forms and urban noise. This interaction is intended to be monitored by urban indicators, comparing the effects of noise propagation in model of urban forms. The model of noise prediction (NMPB96), allowed to develop studies about noise in facades (Ld, level of noise during the day), resulting in colors associated to noise categories. The study will allow the creation of different scenarios and foresee still in the draft fase, the facades exposed to a higher noise level. The effects of noise in facades can be then minimized in advance, by adjusting the layout of their typology.